Weather Prediction Using Indian Almanac Rules - Jawanjal, Kartik; Modi, Mayank; Panchwagh, Aditya; Jadhav, Nagesh (International Journal of Computer Sciences and Engineering, 2021)
Panchang is a traditional Indian Almanac that has been in practice for over 5 millennia. Important meteorological predictions have been fossilised by this method. The Panchang predictions are approximated for a small area, based on astrological occurrences like effects on weather when different celestial bodies come close to one another etc. Panchang consists of 5 components, namely Tithi, Vaara, Nakshatra, Yoga and Karana, along with many different terminologies. Panchang predictions are carried out using some observed rules. Extensive study of these rules has been performed and then an attempt has been made to write a program which incorporates a set of rules and regulations. The main aim was to predict what type of rainfall will be observed on a particular day based on Planetary and Nakshatra positions. A basic implementation of two Panchang types (In python language) has been done. One being Traditional Panchang and the other- Tamil Panchangam. Both the methods mostly use similar rules and logic, but Traditional Panchang allows prediction for a shorter time period accurately and Tamil Panchangam provides accurate predictions for the yearly time period.